Clostridium septicum Gas Gangrene in Colon Cancer: Importance of Early Diagnosis - Sowmya Nanjappa; Sweta Shah; Smitha Pabbathi (Case Reports in Infectious Diseases)
The Clostridia species are responsible for some of the deadliest diseases including gas gangrene, tetanus, and botulism. Clostridium septicum is a rare subgroup known to cause atraumatic myonecrosis and is associated with colonic malignancy or immunosuppression. It is a Gram-positive, anaerobic, spore-forming bacillus found in the gastrointestinal tract and can lead to direct, spontaneous infections of the bowel and peritoneal cavity. The anaerobic glycolysis of the tumor produces an acidic, hypoxic environment favoring germination of clostridial spores. Tumor-induced mucosal ulceration allows for translocation of sporulated bacteria from the bowel into the bloodstream, leading to fulminant sepsis. C. septicum bacteremia can have a variable presentation and is associated with greater than 60% mortality rate. The majority of deaths occur within the first 24 hours if diagnosis and appropriate treatment measures are not promptly started. We report a case of abdominal myonecrosis in a patient with newly diagnosed colon cancer. The aim of this study is to stress the importance of maintaining a high suspicion of C. septicum infection in patients with underlying colonic malignancy.